Factors influencing students' satisfaction towards campus bus services at UTeM - Mangkau, Ivy Deirdre; Mohd Tan, Athirah; P. Jayabalan, Darshanaa (Research and Scientific Innovation Society, 2025)
Transportation services within university campuses are essential for ensuring smooth academic, social, and extracurricular engagement. As student populations grow, campus bus services play a central role in facilitating mobility, yet issues such as unreliable schedules, overcrowding, and inadequate facilities remain common. The research objective about the factors influencing students’ satisfaction towards campus bus services at Universiti Teknikal Malaysia Melaka (UTeM), focusing on two service quality dimensions derived from the SERVQUAL model: facilities of bus and responsiveness. A quantitative descriptive research design was adopted, with data collected from 120 UTeM students through stratified random sampling to ensure representation across faculties and study years. The survey instrument, structured on a 5-point Likert scale, measured student perceptions of bus facilities, responsiveness, and overall satisfaction. Data analysis was conducted using SPSS, incorporating descriptive statistics, reliability tests, normality tests, and Spearman’s rank correlation analysis. The results demonstrated that both facilities and responsiveness significantly affect students’ satisfaction, with facilities showing a very strong relationship correlation (r = 0.708, p < 0.01) and responsiveness reflecting a strong relationship correlation (r = 0.598, p < 0.01). These findings indicate that tangible aspects such as cleanliness, seating comfort, and safety features, alongside intangible aspects like timely communication and attentive driver behavior, are critical to shaping positive student commuting experiences. The study contributes academically by filling the research gap on UTeM’s campus transport system and practically by offering actionable insights for university administrators and transport service managers. Enhancements in bus facilities and improvements in service responsiveness are expected to increase student trust, reduce reliance on private vehicles, and support UTeM’s sustainability objectives.